Role of Spinal Cord α2-Adrenoreceptors in Noradrenergic Inhibition of Nociceptive Transmission During Chemotherapy-Induced Peripheral Neuropathy - Costa-Pereira, José Tiago; Ribeiro, Joana; Martins, Isabel; Tavares, Isaura (Frontiers in Neuroscience, 2020)
Chemotherapy-induced neuropathy (CIN) is a problem during cancer treatment and for cancer survivals but the central mechanisms underlying CIN remain understudied. This study aims to determine if CIN is associated with alterations of noradrenergic modulation of nociceptive transmission at the spinal cord. CIN was induced in male Wistar rats by paclitaxel injections. One month after CIN induction we evaluated the effects of administration of reboxetine (noradrenaline reuptake inhibitor), clonidine (agonist of 𝜶2-adrenoreceptors; 𝜶2-AR) and atipamezole (antagonist of 𝜶2-AR). Furthermore, we measured the spinal levels of the noradrenaline biosynthetic enzyme dopamine-𝜷-hydroxylase (DBH) and of 𝜶2-AR. Reboxetine and clonidine reversed the behavioral signs of CIN whereas the opposite occurred with atipamezole. In the 3 pharmacological approaches, a higher effect was detected in mechanical allodynia, the pain modality which is under descending noradrenergic control. In paclitaxel-injected animals, DBH expression at the spinal dorsal horn was increased. The enhanced recruitment of noradrenergic inhibition during CIN may represent adaptation of noradrenergic pain control noradrenergic centers in the brain to the barrage of peripheral input. A potentiation of the 𝜶2-AR mediated antinociception at the spinal cord may represent a therapeutic opportunity to face CIN.